2016
DOI: 10.1128/jcm.02885-15
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Antibody Detection for Noninvasive Genus-Level Diagnosis of Prosthetic Joint Infection

Abstract: We developed and evaluated a multiplex antibody detection-based immunoassay for the diagnosis of prosthetic joint infections (PJIs). Sixteen protein antigens from three Staphylococcus species (Staphylococcus aureus, Staphylococcus epidermidis, and Staphylococcus lugdunensis) (8 antigens), Streptococcus agalactiae (4 antigens), and Propionibacterium acnes (4 antigens) were selected by comparative immunoproteomics using serum samples from PJI cases versus controls. A bead-based multiplex immunoassay that measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…The sensitivity and specificity of the detection of anti-staphylococcal antibodies in our study are close to those reported by Marmor et al (72.3% and 80.7%, respectively) and lower than those reported by De Seynes et al (87.5% and 93.5%, respectively) [9,10]. The specificity is notably lower than that reported by De Seynes et al with the high number of positive serological reactions among uninfected patients (18.1%) in our study.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The sensitivity and specificity of the detection of anti-staphylococcal antibodies in our study are close to those reported by Marmor et al (72.3% and 80.7%, respectively) and lower than those reported by De Seynes et al (87.5% and 93.5%, respectively) [9,10]. The specificity is notably lower than that reported by De Seynes et al with the high number of positive serological reactions among uninfected patients (18.1%) in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Patients were distributed evenly between PJI and mechanical problems. All PJIs were chronic, with the presence of a sinus tract in a third of cases and a significantly increased CRP level, which reinforces the importance of measuring CRP in the diagnosis of PJI [7][8][9][10].…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations